Influencia de la aplicación de estrategias pedagógicas con enfoque cooperativo en el aprendizaje de los estudiantes de grado 3º de la institución educativa Baudilio Montoya Calarcá Quindío (2017)
Collaborative learning is an approach that allows you to contextualize the situations in which student are whit an environment to optimize individual and group skills from interaction between the students and the teacher. Work in collaborative groups is a tool that benefits the power or learning for students, since in these faced the possibility of providing know ledge, develop skills and training, to learn how to work together with one goal in common. In this research, a work was done with third grade students, which set out work under the collaborative learning approach during the third period of the year 2016, to determine the influence of the application of teaching strategies with this approach in the learning process. This has made a diagnosis of the students, at the beginning of the course in order to compare the results to the end and thus defining the effectiveness of the work done with the students. The analysis of the obtained data gave results which allowed an improvement in the learning of content, especially in those groups of less know ledge at the beginning of the process. It was found that students were able to improve their form of expression, which was reflected in the responses obtained, since they were more coherent and comprehensible. The participation and responsibility in the development of each activity is likewise favored. Thus the collaborative learning can be assumed as a more important as this and effective teaching approach can be used to provide students whit skills for life in society